PERAN AKAD SALAM DALAM MENEKAN RISIKO HARGA DI BANK SYARIAH - Zahir Muhammad Fadhilah Harahap; Miranti Agustina; Try Wahyuni Mawatdah; Muhammad Ikhsan Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze the role of Salam contracts as a sharia financing instrument in reducing price risks in the real sector, particularly agriculture and commodities. Through library research and a qualitative approach, this study examines the basic concepts of Salam contracts, their operational mechanisms in Islamic banking, and their effectiveness in providing price certainty and income stability for producers. The results show that Salam contracts can reduce price volatility by setting prices and specifications for goods at the outset of the contract. In addition, the application of parallel salam, production monitoring, and good risk management strengthen the effectiveness of this contract in dealing with market uncertainty. Thus, Salam contracts not only offer a fair Islamic solution, but also have the potential to become a price stabilization instrument that supports the sustainability of the real sector.